Recommendations of the Polish Paediatric Society, the Polish Society of Vaccinology, and the Polish Society of Family Medicine on meningococcal vaccinations in children and adults in Poland - Ernest Kuchar; Hanna Czajka; Ewelina Gowin; Aneta Nitsch-Osuch; Anna Skoczyńska; Leszek Szenborn; August Wrotek; Jacek Wysocki; Agnieszka Mastalerz-Migas; Jarosław Peregud-Pogorzelski; Teresa Jackowska (Termedia Publishing House, 2022)
Invasive meningococcal disease is a dangerous bacterial infection that often leads to death or permanent disability. Immunization is the best strategy to protect individuals against invasive infections caused by Neisseria meningitidis. The effectiveness of vaccines has been demonstrated in many countries where they have been introduced into national vaccination programs. Meningococcal vaccinations in Poland are recommended in the framework of the National Immunization Program. However, they are not reimbursed, meaning the patient or parent covers vaccination costs. In addition, insufficient public awareness of the disease course and risks associated with meningococcal infection, the need for immunization in the first year of a child's life, the number of doses administered, and the price of the vaccines are barriers to the acceptance and implementation of meningococcal immunization, especially in the youngest children. Recommendations for physicians implementing meningococcal vaccination in children and adults are the result of the work of an expert group.